2019
DOI: 10.1055/a-0859-7276
|View full text |Cite
|
Sign up to set email alerts
|

Association between endoscopic findings of eosinophilic esophagitis and responsiveness to proton pump inhibitors

Abstract: Background and study aims Endoscopic findings of esophageal eosinophilia sometimes localize to small areas of the esophagus. A previous study suggested that pathogenesis of localized-type eosinophilic esophagitis (LEoE) was associated with acid reflux. However, LEoE treatment outcomes have not been studied. We aimed to analyze the clinical and histologic significance of LEoE in comparison with diffuse-type eosinophilic esophagitis (DEoE). Patients and methods This study included 106 patients with eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…Although EoE is known to be common in young to middle-aged men, not only in white populations but also in Japanese populations ( 1 , 25 ), we found a marked male predominance in localized EE compared with diffuse EE in this study. This trend was also shown by another report ( 13 ). Erosive esophagitis, especially mild type, such as grade A or B according to the Los Angeles classification, is significantly more prevalent in young to middle-aged men than in women in Japan ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Although EoE is known to be common in young to middle-aged men, not only in white populations but also in Japanese populations ( 1 , 25 ), we found a marked male predominance in localized EE compared with diffuse EE in this study. This trend was also shown by another report ( 13 ). Erosive esophagitis, especially mild type, such as grade A or B according to the Los Angeles classification, is significantly more prevalent in young to middle-aged men than in women in Japan ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 89%
“…In our present study as well in our previous report, dysphagia and food impaction tended to be less common in patients with localized EE than in those with diffuse EE, but this finding was not statistically significant. Sawada et al reported that asymptomatic patients were more common in the localized group (42%) than in the diffuse group (7%), with statistical significance ( 13 ). Because of the relatively large number of asymptomatic patients included in our diffuse EE group, statistical significance might not have been detected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations